Ankle Brachial Index berhubungan dengan Sensitivitas Kaki Pada Penderita Diabetes Militus Tipe II - Adiputra, I Made Sudarma; Arianta, I Made Dwi; Trisnadewi, Ni Wayan; Oktaviani, Ni Putu Wiwik (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2020)
ABSTRACT Introduction : Chronic hyperglycemia can cause blood vessel endothelial cells and nerve cells to become hyperglycolic. This condition results changes in various biochemical pathways, one of which is protein kinase C (PKC) which causes thickening of the arteries resulting in decreased ABI values. Decreasing the ABI value will disrupt of Schwann cell metabolism, so that it will cause impaired peripheral nerve delivery. Disruption of peripheral nerve delivery will cause a decrease of foot sensitivity. This study aimed to determine the relationship of ankle brachial index (ABI) with foot sensitivity in patient with diabetes mellitus type II in Public Health Center I of South Denpasar. Method : This study used cross sectional method. The number of samples of this research was 86 people collecting by purposive sampling technique. Data were collected used digital spygmonanometer and monofilament 10 g. Result : As many as 23 people with ABI vascular disorders and 42 people with decrease of foot sensitivity. Chi square test results obtained p = 0,000 with a significance value of p<0.05, so 0.000 <0.05 which shows that there is a relationship between ABI and foot sensitivity in patients with diabetes mellitus type II in Public Health Center I of South Denpasar. Discussion : Decrease of ABI value will following with decrease of foot sensitivity, if this isn’t prevented there is a risk of developing diabetic foot in patients with diabetes mellitus type II.